Estrogen Signaling and the Aging Brain: Context-Dependent Considerations for Postmenopausal Hormone Therapy. (7th July 2013) - Mott, Natasha N.; Pak, Toni R.
Abstract : Recent clinical studies have spurred rigorous debate about the benefits of hormone therapy (HT) for postmenopausal women. Controversy first emerged based on a sharp increase in the risk of cardiovascular disease in participants of the Women's Health Initiative (WHI) studies, suggesting that decades of empirical research in animal models was not necessarily applicable to humans. However, a reexamination of the data from the WHI studies suggests that the timing of HT might be a critical factor and that advanced age and/or length of estrogen deprivation might alter the body's ability to respond to estrogens. Dichotomous estrogenic effects are mediated primarily by the actions of two high-affinity estrogen receptors alpha and beta (ER α & ER β ). The expression of the ERs can be overlapping or distinct, dependent upon brain region, sex, age, and exposure to hormone, and, during the time of menopause, there may be changes in receptor expression profiles, post-translational modifications, and protein:protein interactions that could lead to a completely different environment for E2 to exert its effects. In this review, factors affecting estrogen-signaling processes will be discussed with particular attention paid to the expression and transcriptional actions of ER β in brain regions that regulate cognition and affect.